Profile of inborn errors of metabolism among the neonates admitted in special newborn care unit of a tertiary care hospital - Kushal Mandal; Sushama Sahoo; Sarbani Misra; Bharat Lal Kisku (Asian Journal of Medical Sciences, 2025)
Background: Inborn errors of metabolism (IEM) refer to a group of hereditary disorders that occur due to the disruption of normal biochemical processes in the body. Although the incidence of IEM is rare, together their incidence is more than 1:1000.1 IEM usually presents with non-specific symptoms, which could only be ruled out by the presence of a high level of suspicion of the disease. This study shares our experiences of different presentations and incidences of metabolic disorders by doing tandem mass spectrometry and highlights the importance of metabolic screening as a part of routine newborn screening. Aims and Objectives: To study the profile of inborn errors of metabolism among the sick neonates admitted in the special newborn care unit (SNCU). Materials and Methods: This is a hospital-based cross-sectional study done at SNCU of a tertiary care hospital. A total of 100 consecutive newborns with suspicion of IEM were taken as study participants and underwent IEM screening. Results: Out of 100 newborns, the majority were male. Twenty-three newborns were diagnosed with IEM. The most common IEM noted is G6PD deficiency with an overall incidence of 34%, followed by amino acid disorder. Consanguinity shows a significant association with IEM, with an incidence of 72% with a P<0.001. Hypoglycemia (P=0.04) and feed intolerance (P=0.03) also show a significant association with IEM. Conclusion: The incidence of IEM has gradually increased with the advent of metabolic screening. Early diagnosis is crucial with respect to both management and genetic counseling. The higher degree of suspicion can only bring out the actual incidence and improve its outcome.